2015
DOI: 10.3389/fpsyg.2015.00790
|View full text |Cite
|
Sign up to set email alerts
|

Automatic imitation in a rich social context with virtual characters

Abstract: It has been well established that people respond faster when they perform an action that is congruent with an observed action than when they respond with an incongruent action. Here we propose a new method of using interactive Virtual Characters (VCs) to test if social congruency effects can be obtained in a richer social context with sequential hand-arm actions. Two separate experiments were conducted, exploring if it is feasible to measure spatial congruency (Experiment 1) and anatomical congruency (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
(55 reference statements)
9
40
1
Order By: Relevance
“…This finding has wide relevance because avatars, and other visual representations of human figures are now commonly used as stimuli in social and spatial cognition research (e.g., Cole et al, 2015;Kessler & Thomson, 2010;Lawson et al, 2009;Mazzarella et al, 2012;Pan & Hamilton, 2015;Samson et al, 2010;Zacks et al, 2000). The range of animate and inanimate objects that spontaneously generate object-based spatial codes of this nature is indicative of a domain general mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has wide relevance because avatars, and other visual representations of human figures are now commonly used as stimuli in social and spatial cognition research (e.g., Cole et al, 2015;Kessler & Thomson, 2010;Lawson et al, 2009;Mazzarella et al, 2012;Pan & Hamilton, 2015;Samson et al, 2010;Zacks et al, 2000). The range of animate and inanimate objects that spontaneously generate object-based spatial codes of this nature is indicative of a domain general mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar evidence for object-based spatial coding has yet to be demonstrated for observed human figures. Given the ubiquity of avatars, and other visual representations of human figures as stimuli in social and spatial cognition research (e.g., Cole et al, 2015;Kessler & Thomson, 2010;Lawson et al, 2009;Mazzarella et al, 2012;Pan & Hamilton, 2015;Samson et al, 2010;Zacks et al, 2000), the aim of the current study was to employ a modified Simon paradigm in order to examine the nature of the spatial codes spontaneously generated when observing visual whole body depictions of the human figure.…”
Section: Introductionmentioning
confidence: 99%
“…Some laboratories use VR content (i.e., animated 3D avatars) in a semi‐immersive VR display, or even a non‐immersive desktop display (Pfeiffer, Vogeley, & Schilbach, 2013; Sacheli et al ., 2015), sometimes coupled with 3D glasses. These could be considered as augmented reality rather than IVR and provide an interesting bridge between real and computer‐generated worlds (de la Rosa et al ., 2015; Pan & Hamilton, 2015). Although it is arguable that immersion plays a significant role in triggering a realistic reaction in human participants, showing computer‐generated virtual characters on a large screen can also be effective.…”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
“…The choice of which virtual character for advice and whether they followed the advice (i.e., which door they then chose to go through) provided an implicit measure of trust (Hale et al ., 2017). Other studies recorded participants’ hand position during their interaction with a virtual character as a measurement of imitation and found that typical adults automatically imitated the virtual characters, but participants with autism spectrum conditions imitated less (Forbes et al ., 2016; Pan & Hamilton, 2015). These studies illustrate the use of VR to record implicit social behaviours which may be more revealing than traditional key‐hit measures.…”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
“…Whilst previous work has quantitatively examined the kinematic elements of imitative behavior in both healthy people (e.g., Braadbaart et al, 2012;Campione & Gentilucci, 2011;Era et al, 2018;Forbes & Hamilton, 2017;Gold et al, 2008;Hayes et al, 2016;Krüger et al, 2014;Pan & Hamilton, 2015;Reader & Holmes, 2015;Reader et al, 2018;Sacheli et al, 2012;Sacheli et al, 2013, Sacheli, Christensen, et al, 2015Wild et al, 2010;Williams et al, 2013) and brain-damaged patients (e.g., Candidi et al, 2018;Hermsdörfer et al, 1996), as far as we are aware no previous experiments have looked at so many components of the velocity profile in order to compare the coarse-grained (i.e., wrist) kinematic approach to meaningful and meaningless action imitation. Much informative work has been done to assess action performance in meaningful and meaningless action imitation (e.g., Buxbaum et al, 2014;Goldenberg & Hagmann, 1997;Mengotti et al, 2013), but frequently using only subjective rating measures.…”
Section: Kinematics In Meaningful and Meaningless Action Imitationmentioning
confidence: 99%